Application of Onomatopoeia in the Comic “Popeye the Sailorman” Volumes 60-65 (Tamaddun, 2024)
Abstract. This research examines various phonetic symbols in language, such as onomatopoeia, phonesthemes, and ideophones, in the comic *Popeye the Sailorman* volumes 60-65. The study focuses specifically on the forms and meanings of sound symbols, particularly onomatopoeia, as they appear in the comic. This research provides a basis for understanding sound symbols as tools for describing events and conveying the author’s intent to the readers. The objective is to gain a deeper understanding of the role of onomatopoeic sound symbols in the comic’s storyline. For data analysis, the referential identity method (Sudaryanto, 1993) was applied. The types were analyzed by referring to Ullman’s theory (1962). The results show that are two types of onomatopoeias found in the comic, the primary and secondary onomatopoeias. Primary onomatopoeias involves mimicking a sound using a similar sound, where the sound originates from the object itself. This type of onomatopoeia appears in words that imitate sounds, suggesting the object they describe. And Secondary onomatopoeia refers to sounds that emerge from the relationship between an object's sound and its movement (such as dither, dodder, quiver, slink, slither, slouch, squirm, and wriggle) or are solely based on movement. This type of onomatopoeia originates from actions.  The subject of this study is “Popeye the Sailorman”, a comic widely popular with both young and adult readers, especially males or boys. From the volume of 60-65 Popeye comics, 64 types of Onomatopoeai were found. The study’s findings will include a summary, review, and meaningful sentences that will allow the researcher to gain detailed insights into the types, meanings, and unique features of onomatopoeia as they serve to depict events and the storyline of the comic.Keywords : onomatopoeia , sound symbol, comic, linguistic.